Character Internalization Through Structured Habituation in Rural Indonesian Elementary Education - Moh Hirsan; Musipuddin Musipuddin; Lalu Parhanuddin (IJE : Interdisciplinary Journal of Education, 2026)
This study examines how structured habituation supports character internalization among elementary school students in a rural Indonesian school. Using a qualitative case-study design, the research was conducted at SDN 2 Suka Damai, East Lombok, Indonesia. Data were collected through three months of sustained participant observation, semi-structured interviews with the principal, six teachers, and twelve students, and analysis of school program documents. The data were analyzed through iterative coding, data condensation, thematic display, and interpretive verification. Trustworthiness was strengthened through source triangulation, member checking, prolonged engagement, and an audit trail. The findings reveal three main patterns. First, the school implements a layered habituation architecture comprising daily routines, weekly collective activities, and incidental experiential programs that mutually reinforce value cultivation. Second, students' character internalization develops through three overlapping stages: externally regulated compliance, cognitive understanding of moral meaning, and identity-based integration of values. Third, teacher modeling functions as the central relational scaffold that connects repeated routines with deeper moral understanding. This study contributes a context-sensitive model of habituation-based character education by explaining how discipline, responsibility, and honesty are transformed from institutional rules into autonomous student dispositions. The findings offer practical implications for elementary schools seeking to move character education beyond moral instruction toward sustained school culture, teacher credibility, reflective dialogue, and everyday ethical practice.